Murder of a cranky catnapper - Swanson, Denise (Swanson, Denise. Scumble River mysteries., 2016)
School psychologist Skye Denison Boyd opts for pet therapy to aid a handful of socially awkward fourth grade boys with the assistance of the local vet, a Siberian husky, and a Maine coon. When school board member Palmer Lynch is found dead in his home with the therapy cat hidden in his garage, Skye finds herself dealing with a killer.